A case of early-onset congenital syphilitic osteomyelitis of the calcaneus and literature review - Wang Guo; Zhiqun Zhang (BMC, 2024)
Abstract Background Congenital syphilis (CS) is a sexually transmitted disease caused by Treponema pallidum (TP). When the skeletal system is involved, it often results in multiple, symmetrical bone destruction at the epiphyses of long tubular bones such as the humerus and radius, rarely involving the calcaneus. This article reports a case of calcaneal osteomyelitis caused by TP in a child with no other bone damage and subtle clinical manifestations, No similar cases have been reported. Case presentation A 4-month-old male infant presented with right foot swelling without any obvious cause and no history of trauma. X-ray and CT scans showed bone loss in the calcaneus and surrounding soft tissue swelling. Review of past medical records revealed that the infant had been diagnosed with CS infection during a hospital stay for "pneumonia" at one month old. The parents refused surgery, opting for conservative treatment at an external hospital for three weeks, during which the symptoms of the affected foot showed no significant improvement. Subsequently, the child was treated at our hospital with surgery, including lesion removal and cast fixation, followed by oral antibiotic treatment. The last follow-up showed no swelling or tenderness in the affected foot, with good mobility, and X-rays indicated that the bone had essentially returned to normal. Conclusions Early CS rarely involves the calcaneus. When diagnosing unexplained calcaneal osteomyelitis in infants, this rare cause should be considered. A thorough medical history should be taken and a careful physical examination conducted. Once diagnosed, timely surgical debridement and appropriate antibiotic therapy targeting TP infection are required. Early identification and intervention can result in a good prognosis without related complications.